Trends in the learning style of aviation polytechnic cadets during distance learning - Moch. Rifai; Ade Irfansyah; Yuyun Suprapto; Sudrajat Sudrajat; Novita Vindri Harini; Setiyo Setiyo; Asep Muhamad Soleh; Ahmad Fudholi (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
In the era of education 4.0 which is characterized by the use of digital technology, the learning process is not limited to space and time. This allows the implementation of distance learning as a springboard for a new educational model. The Surabaya Aviation Polytechnic is a vocational education institution under the supervision of Direktorat Kelaikudaraan dan Pengoperasian Pesawat Udara (DKPPU). DKPPU as the airworthiness and operation authority has issued letter regarding the online learning system method due to the covid pandemic. One of the determining factors for the success of learning process is the use of appropriate learning media. The choice of learning media influenced by the characteristics of the learner. Therefore, it is important to know the learning styles of students. Thus, this study aims to determine the learning style tendencies of Surabaya Aviation Polytechnic cadets to obtain recommendations for selecting the right media in distance learning. The data collection process involved 900 cadets who were asked to fill out a learning style questionnaire which would later be analyzed quantitatively. For data triangulation, interview sessions were also held for selected cadets. From the results of data analysis, it was concluded that the Surabaya Aviation Polytechnic cadets tended to have visual learning styles (54% or 485 cadets) and auditory (13% or 121 cadets). So, the media recommendations are audio/video tutorials, interactive multimedia, and simulator software. However, a total of 126 cadets do not know their learning styles. They need to be assisted in-class during class learning to increase achievement motivation.